The national project “Labor Productivity” in the Rostov Region: impact on economy of the region - L. A. Pogorelova; M. M. Kulikov (Вестник университета, 2024)
The article analyzes the impact of measures to improve labor productivity within the framework of the national project “Labor Productivity” at enterprises – small businesses of the Rostov region with revenues from 100 to 400 million rubles for the period from 2019 to 2022 inclusive on the aggregate financial performance of companies involved in the project implementation. Based on the analysis of accounting data for the studied set of enterprises, we can conclude about correlation between the measures to improve labor productivity and financial performance within each specific enterprise, as well as in terms of the positive impact on total deductions to the budgets of various levels. It has been shown that total dynamics of payments to the budget for the analyzed period for the studied aggregate increased by 2.2 times, property status of the production complex – by 3.6 times, and profitability indicators – by more than 3 times. Positive influence of the national project “Labor Productivity” on the economy of Rostov region has been proved.   The study results can be used as a basis for adjusting further trajectory of the project implementation in the region, which determines the relevance of the study.